'A critical autoethnography of a doctoral students' research journey: learning to take risks in the academy'. Issue 2 (4th May 2019) - Lynch, Shrehan; Kuntz, Aaron
ABSTRACT: What is missing in present-day physical education teacher education research is the individual female doctoral student perspective and how individuals come to understand academic research culture within the neoliberal university. Through a critical autoethnography, this paper uncovered a transformative learning journey of one doctoral student as she encountered the field of research in higher education. After taking a critically orientated qualitative methods class, the doctoral student recognised that the neoliberal university includes a research agenda entwined in politics, finding that neophyte researchers should be aware of the 'mess' (Cheek, J. (2017). Qualitative inquiry, research marketplaces, and neoliberalism. In N. K. Denzin, & M. D. Giardina (Eds.), Qualitative Inquiry in Neoliberal Times (pp. 19–36). New York: Routledge). By questioning how one is disciplined in research and through becoming aware of normalising techniques, the doctoral student interrogated her research methods and philosophical orientation. Ethnodrama (Denzin, N. K. (2010). The qualitative manifesto . Walnut Creek: Left Coast Press) and autoethnography provided the doctoral student with an opportunity for alternate meaning-making, which can be productive in understanding the journey of becoming in academia.